The Effects of Music Intensity on Performance and Cardiovascular Responses in Athletes - Paria Torkamandi; Ali Akbarnejad; Abbas Ali Gaeini; Ali Gharecheshmei Ghahremanloo (Sport Sciences and Health Research)
Introduction: The current study aimed to evaluate the effects of different musical intensities on performance and cardiovascular responses after incremental exercise in male athletes. Materials and Methods: In this quasi-experimental study with a cross-over design, 15 male athletes were voluntarily selected. The study subjects performed Bruce protocol, along with listening to progressive music, slow music, and without music until exhaustion. Results: This study indicated that systolic and diastolic blood pressure, maximum oxygen consumption, maximum heart rate, and time to exhaustion insignificantly decreased while listening to slow music, compared to the no music (P=0.134, P=0.993, P=0.999, P=0.160, P=0.819, respectively). Furthermore, while listening to progressive music, compared to no music, the systolic and diastolic blood pressure, as well as maximum heart rate insignificantly increased (P=0.735, P=0.999, P=0.496, respectively); the maximum oxygen consumption and the time of exhaustion significantly increased in the study subjects (P=0.043, P=0.008 respectively). Moreover, while listening to progressive music, compared to slow music, the systolic blood pressure, maximum oxygen consumption, maximum heart rate, and the time of exhaustion significantly increased (P=0.004, P=0.009, P=0.002, P=0.001 respectively); however, diastolic blood pressure presented an insignificant decrease (P=0.253). Conclusion: The obtained findings revealed that listening to progressive music can affect physiological factors and performance during exercising. It increases the athlete’s motivation and postpones the time to exhaustion to continue exercising; however, listening to slow music creates a state of relaxation during exercise and reduces heart rate. As a result, individuals with hypertension can decline their blood pressure during endurance exercise by listening to soft music.